2019
DOI: 10.5933/jkapd.2019.46.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Age Assessment of SMI and MP3 Stages to Predict the Pubertal Growth Spurt

Abstract: This study aimed to assess the skeletal age of skeletal maturational indicator (SMI) and middle phalanx of the middle finger (MP3) stages and to predict the SMI and MP3 stages corresponding to pubertal growth spurt in boys and girls respectively.The skeletal age was assessed from hand-wrist radiographs of 363 children (182 boys, 181 girls) aged 7 to 16 years by radiologists using the Korean standard bone age chart. Also, SMI and MP3 stages were evaluated from the radiographs. From these records, the mean skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…A recent Korean study showed that the plateau of the pubertal growth spurt was at 14 years in girls and at 16 in boys 25 , 32 . The maximal growth velocity has tended to be faster 25 ; therefore, 14 would be a better cutoff for Korean children to distinguish ages in volumetric growth from maturation periods. Age under 20 could suggest late physical maturation and end of adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Korean study showed that the plateau of the pubertal growth spurt was at 14 years in girls and at 16 in boys 25 , 32 . The maximal growth velocity has tended to be faster 25 ; therefore, 14 would be a better cutoff for Korean children to distinguish ages in volumetric growth from maturation periods. Age under 20 could suggest late physical maturation and end of adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were divided into three age categories: (1) age under 14 years, (2) age ≥ 14 years and < 20 years, and (3) ≥ 20 years. Age 14 is considered to be the age of the last growth spurt in Korean children 25 , and age 20 is the border between adolescence and adulthood in the WHO classification 26 . Patient distribution according to age categories is described in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported on the stage of peak height velocity in SMI and MP3 classification. Hägg and Taranger [9] considered SMI stage 6 as the maximum growth period and according to studies on Koreans, Kim et al [24] reported that males are most commonly found in SMI stages 5 -7 and females in stages 6 -7, whereas Lee and Mah [25] reported that males are found in SMI stages 4 -5 and the MP3 FG -G stage and females in SMI stages 3 -4 and the MP3 F -FG stage. To improve the accuracy of growth prediction, it is recommended that additional morphological, biological, and genetic indicators be evaluated [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…This study had a limitation related to the lack of interpretation on SMI 7 -9 stages whether corresponding to the mid- Although the hand -wrist radiograph is the most common method to evaluate the skeletal development due to its objective and simple interpretation, high reproducibility, and minimal radiation exposure, it is not yet described as an absolute "gold standard" for the skeletal maturity [28]. As a result, if more studies on prediction of midpalatal suture maturation with various other methods to assess the skeletal maturity will be proceeded, the midpalatal suture maturation can be more accurately determined.…”
Section: ⅳ Discussionmentioning
confidence: 99%